Pattern Recognition Receptor Signaling and Innate Responses to Influenza A Viruses in the Mallard Duck, Compared to Humans and Chickens - Campbell, Lee K.; Magor, Katharine E. (Frontiers in Cellular and Infection Microbiology, 2020)
Mallard ducks are a natural host and reservoir of avian Influenza A viruses. While most influenza strains can replicate in mallards, the virus typically does not cause substantial disease in this host. Mallards are often resistant to disease caused by highly pathogenic avian influenza viruses, while the same strains can cause severe infection in humans, chickens and even other species of ducks, resulting in systemic spread of the virus and even death. The differences in influenza detection and antiviral effectors responsible for limiting damage in the mallards are largely unknown. Domestic mallards have an early and robust innate response to infection that seems to limit replication and clear highly pathogenic strains. The regulation and timing of the response to influenza also seems to circumvent damage done by a prolonged or dysregulated immune response. Rapid initiation of innate immune responses depends on viral recognition by pattern recognition receptors (PRRs) expressed in tissues where the virus replicates. RIG-like receptors (RLRs), Toll-like receptors (TLRs) and Nod-like receptors (NLRs) are all important influenza sensors in mammals during infection. Ducks utilize many of the same PRRs to detect influenza, namely RIG-I, TLR7 and TLR3 and their downstream adaptors. Ducks also express many of the same signal transduction proteins including TBK1, TRIF and TRAF3. Some antiviral effectors expressed downstream of these signalling pathways inhibit influenza replication in ducks. In this review, we summarize the recent advances in our understanding of influenza recognition and response through duck PRRs and their adaptors. We compare basal tissue expression and regulation of these signalling components in birds, to better understand what contributes to influenza resistance in the duck.